Predição de eventos cardiovasculares em hipertensos e normotensos com anatomia coronariana conhecida e isquemia miocárdica - Teles, Cláudia Patrícia Souza (2015)
Introduction: Cardiovascular diseases are the main causes of morbidity and mortality in the world. They account 18 million deaths a year; coronary atherosclerotic disease (CAD) and cerebrovascular disease (CVD) account for 2/3 of these, and about 22% of the 55 million deaths from all causes. Among its modifiable risk factors, systemic arterial hypertension (SAH) is considered of great value. However, there is a linear relationship between the risk of death because of vascular causes and blood pressure values, even within the normal range. Objectives: Evaluate the prediction of major cardiovascular events (ECM) in normotensive (Nts) and hypertensive (Hts) patients, with known coronary anatomy and myocardial ischemia detected by the exercise stress echocardiography (ESE ); and compare clinical characteristics, anthropometric, ergometric, echocardiographic and coronary angiography between groups. Patients and Methods: This was a retrospective cohort of 423 patients (Nts = 143 and Hts = 280) who underwent ESE from January 2001 to November 2014 and subsequently underwent to a coronary angiography. The event search was conducted by telephone calls and active search for information in outpatient medical records of their physicians. On the statistical analysis, categorical variables were analyzed by chi-square test. Numeric variables presented in mean and standard deviation. For normal distribution, we used the Student t test. Were also used survival Kaplan-Meier curves, log-rank test and Cox regression models. We adopted two-tailed value significance criterion of p <0.05. Results: The mean age of patients was 58.8 ± 10.9 years, and 208 (49.2%) men and 215 (50.8%) women. When comparing Nts and Hts, there was difference in age (55.76 ± 11.4 and 60.36 ± 10.39; p <0.0001), BMI (26.44 ± 3.6 and 28.42 ± 4.53; p <0.0001), diabetes mellitus [17 (22.97%) and 57 (77.03%); p = 0.03], dyslipidemia [(82 (27.06%) and 221 (72.94%), p <0.0001], previous myocardial revascularization [(7 (17.07%) and 34 (82, 93%), p = 0.01], family history of CAD [(79 (28.83%) and 195 (71.17%), p = 0.003], use of ACE inhibitors or ARBs [5 (2.04% ) and 240 (97.96%), p <0.0001] and beta-blockers [26 (22.61%) and 89 (77.39%);. p = 0.003] The Hts had higher left ventricular mass index (89.86 ± 23.88 and 96.94 ± 24.99, p = 0.005), lower stage reached in treadmill (3.03 ± 1.05 and 2.68 ± 0.97, p = 0.004) and an increased prevalence of CAD (28.57% vs. 71.43%, p = 0.008). There were 103 events, 25 (24.3%) in Nts and 78 (75.7%) in Hts whereas dichotomous variable event, Hts had frequently than Nts (17.48% vs. 27.86%, p = 0.019). Kaplan-Meier survival curve showed a significantly worse prognosis not only in Hts group, but also in patients with CAD. In log-rank test to stratify occurrence of events for CAD, the difference between Nts and Hts disappeared. In Cox regression stratified for CAD, only males were statistically significant. Conclusion: Although Hts have presented more events, independent of blood pressure levels in both predictors of cardiovascular events and CAD groups were males.